The Burden of Comorbidities in Saudi Arabia: Systemic Disease Patterns and Their Predictive Value for Mortality - Syed Mohammed Basheeruddin Asdaq, (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Chronic diseases are increasingly straining healthcare systems worldwide, with comorbidities substantially impacting morbidity and mortality in Saudi Arabia. While chronic disease management remains a priority, limited research has explored comorbidity-mortality relationships in the Saudi context. This study examines comorbidity prevalence and its potential mortality associations within the Saudi population. Materials and Methods: This retrospective crosssectional study analyzed electronic health records to examine associations between mortality and demographic/clinical variables (age, gender, marital status, employment, comorbidities). Using both parametric (Analysis of variance) and nonparametric (Mann-Whitney U) tests with 95% confidence intervals (CIs) (P < 0.05), we conducted correlation analyses to identify significant mortality predictors. Results: The study population encompassed a wide age range, with 52.3% of participants being male, 70.3% married, and 68.3% employed. Approximately 39% of participants had one or more comorbidities. Key predictors of comorbidities included advanced age (34.6%), circulatory system diseases (20.3%), and nervous system disorders (12.1%). Correlation analysis revealed significant associations between age (odds ratio [OR] = 1.15; 95% CI = 1.39–0.83; P < 0.05), the presence of comorbidities (OR = 1.33; 95% CI = 1.53–0.72; P < 0.05), and the number of comorbidities (OR = 1.63; 95% CI = 1.87–0.93; P < 0.001). Comorbid conditions associated with the circulatory system (Rho = 0.62), external causes (Rho = 0.48), and the respiratory system (Rho = 0.41) had a significant (P < 0.05) influence on mortality. Furthermore, advanced age was identified as the highest risk factor for mortality (Rho = 0.93, P < 0.05). Conclusion: Age, the presence of comorbidities, and the number of comorbid conditions were identified as major contributors to mortality in the Saudi population. These findings underscore the importance of addressing these factors in healthcare strategies, with a focus on promoting lifestyle changes, smoking cessation, regular medical screenings, and infection prevention to improve public health outcomes.